ZnSxSe1−x thin films: A study into its tunable energy band gap property using an experimental and theoretical approach. (1st July 2022) - Ray, Subhasmita; Barman, Biswajit; Darshan, C; Tarafder, Kartick; Bangera, Kasturi V.
Highlights: Ternary compositions of ZnSxSe1-x thin films were deposited using a thermal evaporation technique and the various properties of the films were explored using both experimental and theorical studies. All the films obtained exhibited good crystallinity and morphology. The material geometry was determined using Density Functional Theory (DFT) calculations, whereas Quantum ATK package was used to calculate the theoretical optical properties of the films. A successful band gap engineering (2.59–3.38 eV) was achieved experimentally for the ternary alloy and the same was later confirmed from the theoretical studies. Abstract: In recent times, ZnS and ZnSe thin films are drawing tremendous attention towards opto-electrical devices due to their optimal wide band gap energy. By alloying ZnS and ZnSe films to obtain ZnSx Se1−x thin films, the band gap of the ZnSx Se1−x film can be tuned to a value according to the device requirements. Herein, ZnSx Se1−x thin films were deposited on pre-cleaned glass substrates using a thermal evaporation system and the various properties of the obtained thin films were analyzed by altering the percentage of sulfur concentration in the films. The XRD analysis illustrated that the prepared films are polycrystalline in nature and oriented along cubic (1 1 1) plane. The deviation of (1 1 1) preferential peak position with composition 'x' along the absence of any secondary peaks confirms the formation of ternary ZnSx Se1−x thin films. DFT analysis verifies the formation of pristine ZnSx Se1−x alloy system. FESEM micrographs displayed that the ZnSx Se1−x thin films do not have any cracks or pinholes. EDAX analysis of the films revealed the existence of Zn, Se and S in an appropriate quantity. Optical analysis revealed the effective band gap tailoring of ZnSx Se1−x thin films. The band gap of the ZnSx Se1−x thin films increases from 2.59 eV to 3.38 eV as the composition 'x' varied from 0 to 1 and band composition was determined using the DOS plot obtained using VASP.